Pemanfaatan Alat Peraga IPA Sederhana untuk Menunjang Pembelajaran IPA pada Materi Sistem Eksresi pada Manusia - Ana Seftia Andriani; Ramlawati Ramlawati; Sitti Rahma Yunus; Sabriani Sabriani (Program Studi Pendidikan IPA Fakultas MIPA Universitas Negeri Makassar, 2024)
The use of media increases students' interest in the material being taught so that learning is more interactive. The teaching and learning process designed and implemented by the teacher should attract the attention of students. The process of teaching and learning activities that are not interesting can cause boredom and boredom in students which will result in student learning achievements. This service aims to find out and increase students' interest in learning by utilizing Simple Science teaching aids. The output of this training is the level of student satisfaction with the use of Simple Science teaching aids. The research was conducted at UPT SMPN 1 Pinrang with a total of 22 students who indicated that the results of satisfaction led to positive aspects in the use of simple science teaching aids in science learning.